Spatial Planning and Development of the Miftahul Ulum Islamic Boarding School Area in Rasau Jaya District, Kubu Raya Regency - Nizar; Reski, Indah Anjar; Fuaddi, Azka Rahmat; Hutasoit, Marsyauli (International Journal of Research in Vocational Studies (IJRVOCAS), 2026)
The Miftahul Ulum Islamic Boarding School (Pondok Pesantren), located in Rasau Jaya District, Kubu Raya Regency, faced problems related to limited facilities and suboptimal spatial arrangement. This condition caused discomfort for students (santri) in their daily activities, including aspects of accommodation, learning, and worship. This research aimed to plan and arrange the pesantren area in an integrated manner by developing a site plan, planning supporting infrastructure, and calculating the estimated budget for the construction of the male dormitory. The research method included a literature review, a field survey, and an analysis of space requirements based on applicable technical standards. The collected data were analyzed descriptively to illustrate the existing conditions, followed by zoning planning for the area using the reference standard SNI 03-1733-2004, and budget calculation based on unit price analysis appropriate to local conditions. The results of the study proposed the division of the area into three zones: public, semi-private, and private, supported by educational, worship, accommodation, and ancillary facilities. The Bill of Quantity (BOQ) calculation showed the estimated cost needed for the construction of the student dormitory, which can serve as a guide for implementation. In conclusion, this research suggests that integrated planning and arrangement of the pesantren area are capable of creating a more organized, comfortable, and sustainable learning environment.